Comparative hindlimb bone morphology in noctilionid fisher bats (Chiroptera: Noctilionidae), with emphasis on Noctilio leporinus postnatal development - Reyes Amaya, Nicolás Rafael (2018)
The hindlimbs allow bats to attach to the mother from birth, and roost during independent life. Despite the great morphological diversity in Chiroptera, the hindlimbs morphology and its postnatal development have been poorly studied. Postnatal development of hindlimbs in Noctilio leporinus is described, further comparing the morphology of adults with that of Noctilio albiventris and previously reported species (Desmodus rotundus, Artibeus lituratus, Molossus molossus). The ossification ending sequence at autopodium elements of N. leporinus does not follow the distal to proximal directional sequence described for D. rotundus, exhibiting a heterochronic delayed ossification ending for the digits of N. leporinus regarding other hindlimb elements, associated with the bigger relative autopodium size of this fisher bat regarding other bat species. Noctilionid bats share the same adult hindlimb bone morphology, except for differences at hindlimb proportions and calcar ossification degree. There are differences in the number and position of bony processes, slots and sesamoids of adult noctilionid fisher bats regarding previously reported species; most differences are concentrated at the autopodium and are related to an increased surface for muscular insertion and the structural support of claws. These facts seem to be closely associated with functional demands of the feeding strategy of noctilionid fisher bats.